Ten Color Multiparameter Flow Cytometry in Bone Marrow and Apheresis Products for Assessment and Outcome Prediction in Multiple Myeloma Patients - Riebl, Veronika; Dold, Sandra Maria; Wider, Dagmar; Follo, Marie; Ihorst, Gabriele; Waldschmidt, Johannes M.; Jung, Johannes; Rassner, Michael; Greil, Christine; Wäsch, Ralph; Engelhardt, Monika (Frontiers in Oncology, 2021)
Objective: In clinical trials (CTs) the assessment of minimal residual disease (MRD) has proven to have prognostic value for multiple myeloma (MM) patients. Multiparameter flow cytometry (MFC) and next-generation sequencing are currently used in CTs as effective tools for outcome prediction. We have described 6- and 8-color MFC panels with and without kappa/lambda, which were equally reliable in detecting aberrant plasma cells (aPC) in myeloma bone marrow (BM) specimens. This follow-up study a) established a highly sensitive single-tube 10-color MFC panel for MRD detection in myeloma samples carrying different disease burden (monoclonal gammopathy of unknown significance (MGUS), smoldering multiple myeloma (SMM), MM), b) evaluated additional, rarely used markers included in this panel and c) assessed MRD levels and the predictive value in apheresis vs. BM samples of MM patients undergoing autologous stem cell transplantation (ASCT). Methods + Results: The 10-color MFC was performed in BM and apheresis samples of 128 MM and pre-MM (MGUS/SMM) patients. The markers CD28, CD200, CD19 and CD117 underwent closer examination. The analysis revealed distinct differences in these antigens between MM, MGUS/SMM, and patients under treatment. In apheresis samples, the 10-color panel determined MRD negativity in 44% of patients. Absence of aPC in apheresis corresponded with disease burden, cytogenetics and response to induction. It also determined MRD negativity in BM samples after ASCT and was associated with improved progression free survival. Conclusion: These results highlight the significance of the evaluation of both BM and apheresis samples with a novel highly sensitive 10-color MFC panel.